2018
DOI: 10.3892/ol.2018.9863
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA hsa_circ_0078602 may have potential as a prognostic biomarker for patients with hepatocellular carcinoma

Abstract: Circular RNA (circRNA), a type of endogenous non-coding RNA, is a closed continuous loop of RNA with no poly(A) tail. Previously, studies have identified that circRNAs are closely associated with several cancer types. However, their function in hepatocellular carcinoma (HCC) has rarely been studied. Therefore, the aim of the current study was to screen differential circRNA expression between HCC tissues and adjacent non-cancerous tissues, and test the potential clinical value of individual circRNAs. CircRNA mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 40 publications
(39 reference statements)
0
17
0
Order By: Relevance
“…recent studies have indicated that circrnas may serve important roles in driving cancer initiation and progression, and have the potential to serve as biomarkers for predicting cancer progression (7,8). accumulating evidence has demonstrated that circrnas regulate Hcc progression and serve as potential biomarkers for predicting cancer prognosis (9)(10)(11)(12)(13)(14)(15). However, a considerable number of circrnas remain to be elucidated in Hcc.…”
Section: Introductionmentioning
confidence: 99%
“…recent studies have indicated that circrnas may serve important roles in driving cancer initiation and progression, and have the potential to serve as biomarkers for predicting cancer progression (7,8). accumulating evidence has demonstrated that circrnas regulate Hcc progression and serve as potential biomarkers for predicting cancer prognosis (9)(10)(11)(12)(13)(14)(15). However, a considerable number of circrnas remain to be elucidated in Hcc.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al discovered that circRNA‐100338 could serve as a prognostic indicator for HCC. KOU et al demonstrated that hsa_circ_0078602 expression level was linked to prognosis among patients with HCC.…”
Section: Discussionmentioning
confidence: 99%
“…CDR1as promotes HCC progression by activating PI3K/AKT/mTOR pathway by sponging miR-7 (Xu et al, 2017). Circ_0078602 was downregulated in HCC tissues and was associated with poor prognosis (Kou et al, 2019). CircC3P1 was also downregulated in HCC and was negatively correlated with TNM stage, tumor size, vascular invasion, and lower OS in HCC patients (Zhong et al, 2018).…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%